Steinbeck family - unknown:::Creator::::::::::::
The Steinbeck family at the beach for an outing. Inscription on back reads "Beach outing, John father (John Ernst) and mother (Olive), holding up hat; Elizabeth (sister) standing behind John; Esther (sister) to the right of Elizabeth."